2011
DOI: 10.1016/j.actpsy.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The relation between body semantics and spatial body representations

Abstract: The present study addressed the relation between body semantics (i.e. semantic knowledge about the human body) and spatial body representations, by presenting participants with word pairs, one below the other, referring to body parts. The spatial position of the word pairs could be congruent (e.g. EYE / MOUTH) or incongruent (MOUTH / EYE) with respect to the spatial position of the words' referents. In addition, the spatial distance between the words' referents was varied, resulting in word pairs referring to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…This finding are in line with the idea of a standard representation, however physical constraints certainly forced the creation of such preferences. Our findings bring the idea of a standard posture to a different level that extends beyond the rigid anatomical or gravitational constraints (van Elk & Blanke, 2011; Yamamoto & Kitazawa, 2001; de Haan et al, 2012; Heed et al, 2012), pointing toward a stable standard hand posture that could potentially extend to other body parts. The standard posture would not be based on physical constraints (or not only at least), but on functional advantages.…”
Section: Discussionmentioning
confidence: 59%
“…This finding are in line with the idea of a standard representation, however physical constraints certainly forced the creation of such preferences. Our findings bring the idea of a standard posture to a different level that extends beyond the rigid anatomical or gravitational constraints (van Elk & Blanke, 2011; Yamamoto & Kitazawa, 2001; de Haan et al, 2012; Heed et al, 2012), pointing toward a stable standard hand posture that could potentially extend to other body parts. The standard posture would not be based on physical constraints (or not only at least), but on functional advantages.…”
Section: Discussionmentioning
confidence: 59%
“…These integrative cognitive processes typically include two different body representations: body image and body schema (Longo et al., 2009). Body image is the perception of one's body—name, size, shape, and judgements—and contributes to defining identity/self and is made up of a series of cognitive, perceptual, affective and behavioural components (De Vignemont, 2010; Tsakiris et al., 2011; van Elk & Blanke, 2011). In contrast, body schema is predominantly somatosensory and is defined as “the awareness of a specific body part's movement” (Gadsby, 2017; Morasso & Mohan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies interpreted the presence of an analogous distance effect when processing body parts stimuli, by tracing it back to mental imagery strategies (Van Elk & Blanke, 2011). That is, participants may scan a mental image of the body while performing the task, hence in turn relying on visuo-spatial experience with the body (e.g., Noordzij & Postma, 2005;Peviani et al, 2019;Struiksma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies have reported a (spatial) distance effect when processing body part terms (e.g., Van Elk & Blanke, 2011), with pairs of words describing closer body parts (e.g., "nosemouth") being processed faster as compared with pairs of words describing body parts located farther apart (e.g., "ear -knee"). Evidence for a similar distance effect in body representation has been demonstrated when participants are asked to judge the relative distance between body parts (Smeets et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation